Desain and Construction Hybrid System of PLN-PV-Battery in the Receiver Box Package Based Internet of Things - Rachmad Ikhsan; Inzar Salfikar; Ramadhani (Jurnal Inotera, 2023)
In previous research, if there was a power outage from PLN, the electrical system in the package receiving box experienced problems, so that the package courier could not access the package receiving box. The purpose of making this tool is to overcome electrical supply failures in IoT-based package receiving boxes. The system designed uses voltage sensors connected to each source of electrical energy from PLN, Photovoltaic (PV) and also batteries. After that, the voltage sensor gives a signal to the Arduino for the switching process to be carried out on each source of electrical energy. This system works, if there is a power outage from PLN, the electrical energy is supplied via PV. If the PV voltage is not sufficient, the electrical system will be supplied via batteries, so that the electrical energy in the package receiving box will always be available and can work even if there is a power outage from PLN. Based on the hybrid system test results, it was found that the voltage sensor works by detecting voltage from each source of electrical energy. When the voltage sensor does not detect a voltage source from PLN, the system will switch to PV, when the voltage sensor on the PV detects a voltage below 10 Volts, then the system will switch to battery.